Increasing importance of China in the world politics and its influence on Turkey - Satıcı, Bülent (My University, 2002)
Çin birçok değerlendirmeye göre 21. yüzyılın dünya politikasında önemi sürekli artan bir aktörüdür . 10 milyon kilometre kare toprağı ,1,3 milyar nüfusu ile Çin dev bir ülkedir. Büyüklüğüne bağlı olarak da dünya dengelerini olumlu veya olumsuz olarak hem genel olarak hem de özel bazı ülkeler için etkileyebilme potansiyeli taşımaktadır . Çin bugün siyasal istikrarı , son yirmi yıldaki makro ekonomik kriz yaşamaksızın gösterdiği etkileyici büyüme performansı , askeri modernizasyon hareketi, sosyo-ekonomik alanda attığı adımlar ,uluslararası kurumlardaki aktif rolü ile bundan da çok daha fazlasıdır. Çin uluslararası hem Asya-Pasifik bölgesi hem de tüm dünya için topluluğun öne çıkan bir üyesi olmaktadır. Gözüken odur ki uluslararası topluluğun diğer önde gelen üyeleri de Çin'in uluslararası düzene entegrasyonunu kabul etme eğilimindedirler . Çin'in DTÖ üyeliği dünya ticaret sistemine Çin'in de entegre olması manasına gelir ki bu Çin'in son yirmi yıldaki ekonomik büyüme performansını sürdürebilmesi için çok önemlidir . Çin ekonomisinin büyüklüğü , üretim profili dolayısıyla Çin'in dünya serbest ticaret düzenine eklemlenmesi genelde onunla rekabet etmek zorunda kalacak ülkeler özelde de Türkiye için zor olacaktır . Çin'in DTÖ üyeliği Türkiye gerekli adımları atmadığı ölçüde Türkiye'nin makro ekonomik istikrarını tehdit edecektir . Bu çalışma Çin'in dünya konjonktüründe artan önemini ve dünya dengeleri ve Türkiye üzerinde etki yapma potansiyelini ekonomik bakış açısı ile anlamaya çalışmaktadır . Türkiye üzerindeki etkiler Türkiye'nin tekstil ihracatına yapacağı etkiler anlatılarak yapılmaktadır . China is an increasingly important actor of international politics of twenty first century for various considerations. China is a giant country with its roughly 10million square kilometers territory and 1,3 billion population. Thanks to its size, this country has the potential to produce significant influences both on global balances among countries of international community and on individual countries directly or indirectly. To day China is even much more than this with its political stability, very impressive economic development in the last twenty years with macro economic stability, important steps taken in socio-economic, political, administrative, military modernizations, active role playing in many international organizations with political, economic, security considerations. China is becoming one of the predominant actors of international community not only for Asia-Pacific region but also whole world. It seems other predominant actors of international community is willing to accept China into the existing global system based on the idea that not to do this might mean creation of a destructive actor against international peace and stability . Accession of China into WTO can be considered as integration of China into global trade system which is vitally important for Chinese growth strategy to keep its impressive performance in the last twenty years. It is safe to claim that due to the size of its economy and production profile, integration of China into global liberal trade system will mean hard times for some countries who have to compete against China, Turkey might be one of these countries. Accession of China into WTO can be considered as a serious threat for macro economic stability of Turkey unless Turkey can take necessary steps to ease the situation herself. This study tries to analyze the potential China has, to produce significant influences both on global balances and on Turkey, tries to understand China as an increasingly more important actor of international politics, tries to understand the China of near future and its possible influences on Turkey from an economical point of view in relationship to the macro economic stability of Turkey particularly for textile exports which is critical for Turkey to preserve its macro economic stability. 1
Keywords: Ekonomi_Çin Halk Cumhuriyeti